The Relation between Spoken and Written Language - Анусас, П. (Kalbotyra, 1981)
Language can be manifested in two forms: i.e. writing and speech. The distinction between the two should be maintained for methodological reasons, in addition to the relevance it has for general linguistics.In the present article an attempt has been made to delimit the notion “spoken language”, and a different descriptive framework (the levels and units of analysis) of the equipollent media bas been tentatively suggested.